Pengaruh Kemampuan Komunikasi Interpersonal terhadap Stabilitas Pernikahan: Kasus pada Pasangan Usia Perkawinan 0-5 Tahun di Kota Bekasi - Nurfadliyah, Nadia; Maryam, Siti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
In the marriage that experiences adjustments at the beginning of the married couples aged 0-5 years, interpersonal communication is very important so that the relationship can develop and stabilize. This initial period is prone to conflict due to differences that must be adjusted between partners. Interpersonal communication skills are important in this critical period to understand each other and reduce the possibility of problems that can affect marital stability. This study aims to determine the effect of interpersonal communication skills on the marital stability of married couples aged 0-5 years in Bekasi City using social penetration theory. Social penetration theory illustrates that self-disclosure and changes in communication can deepen a relationship, allowing it to develop from a more casual to a more intimate connection. Quantitative explanatory methodology was used in this study. The results obtained showed that there was a positive influence of 40.7% and a significance of 0.000 < 0.05 from interpersonal communication skills on the marital stability of married couples aged 0-5 years in Bekasi City. It can be concluded that there is a significant effect of interpersonal communication skills on the marital stability of married couples aged 0-5 years in Bekasi City.